2015
DOI: 10.1002/chem.201406428
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Colloidal Dispersions of Vanadium Tetrasulfide (VS4)

Abstract: Although many of the layered metal chalcogenides, such as MoS2, are well-studied, some other chalcogenides have received less attention by comparison. In particular, there has been an emerging interest in vanadium tetrasulfide (VS4), which displays useful properties as a component of hybrids. However, the synthetic methods and characteristics of individual VS4 are not yet well defined, and there is no report on its solution processability. Here we have synthesized VS4 by a simple and fast direct reaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…Among all of the reported anode materials for SIBs, V‐based sulfides have attracted attention owing to their high reversible capacities resulting from the large Na + storage spacing and the polytropic valence of V ranging from +5 to 0 . VS 4 , as a cheap and environmentally benign mineral (Patronite), is a potential electrode material for application in SIBs, owing to its unique structural characteristics of large interchain distance (5.83 Å) caused by parallel 1 D chains, weak interaction between neighboring chains caused by weak van der Waals forces, and high content of S − caused by S 2 2− monomer . These characteristics can not only afford enough potential sites for Na + storage with the theoretical specific capacity of 1196 mAh g −1 for VS 4 +8 Na + +8 e − ⇄4 Na 2 S+V, but also contribute to Na + transfer in the chains.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Among all of the reported anode materials for SIBs, V‐based sulfides have attracted attention owing to their high reversible capacities resulting from the large Na + storage spacing and the polytropic valence of V ranging from +5 to 0 . VS 4 , as a cheap and environmentally benign mineral (Patronite), is a potential electrode material for application in SIBs, owing to its unique structural characteristics of large interchain distance (5.83 Å) caused by parallel 1 D chains, weak interaction between neighboring chains caused by weak van der Waals forces, and high content of S − caused by S 2 2− monomer . These characteristics can not only afford enough potential sites for Na + storage with the theoretical specific capacity of 1196 mAh g −1 for VS 4 +8 Na + +8 e − ⇄4 Na 2 S+V, but also contribute to Na + transfer in the chains.…”
Section: Introductionsupporting
confidence: 72%
“…Compared with PP‐VS 4 and PB‐VS 4 , SB‐VS 4 has a smoother XRD pattern and higher (1 1 0) diffraction peak at 15.78° relative to other diffraction peaks, better revealing its high‐crystallinity feature and dominated crystal growth along (1 1 0) crystallographic direction. All Raman spectra appear very similar with seven peaks located at 141, 191, 281, 406, 521, 688, and 992 cm −1 (Figure S2 a), which are induced by the bending and stretching vibrations of V−S bonds or their combination . When compared to their FTIR database in Figure b, the v (V−S−V) doubly bonded S 2− and the ν (V=S) terminal S stretches of VS 4 are obviously probed at 545 and 990 cm −1 , respectively .…”
Section: Resultsmentioning
confidence: 93%
“…[19] The Raman scattering pattern of VS 4 @GS-2 showed bands located at 190 and 279 cm À1 ,w hich corresponded to the VÀSb onds tretching (A 1 )a nd bending (B 1 )v ibrations, respectively ( Figure 1c). [20] Aw eak, broad peak waso bserved at approximately 870 cm À1 ,w hich was caused by the VÀCl inkage between GSs and VS 4 . [21] The Raman patterns of VS 4 @GS-2 and GO between 1150 and 1800 cm À1 showedt wo strong peaks at 1345 and1 591 cm À1 ,w hich werea ttributed to ad isordered carbon-inducedDband and the graphite-related Gb and, respectively.T he correspondingD /G intensity ratio of VS 4 @GS-2 (D/G = 1.13:1) was substantially higher than that of GO (D/G = 1.05:1), which was consistentw ith the formation of graphene possessing some defects and disordered structures.…”
Section: Resultsmentioning
confidence: 98%
“…Notably, GO was a requirement for VS 4 formation because VS 2 was obtained in the absence of GO (Figure S1, Supporting Information), which indicated that the GO template was essential in this synthetic process . The Raman scattering pattern of VS 4 @GS‐2 showed bands located at 190 and 279 cm −1 , which corresponded to the V−S bond stretching (A 1 ) and bending (B 1 ) vibrations, respectively (Figure c) . A weak, broad peak was observed at approximately 870 cm −1 , which was caused by the V−C linkage between GSs and VS 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure S2 shows the full scan survey of VS 2 NDs, which reveals the existence of vanadium and sulfur elements. 37,38 Besides, a small shoulder peak at 514.40 eV was noted and could be assigned to V 3+ 2p 3/2 state. Figure 5A,B displays V 2p core level spectra after deconvolution for as-prepared and annealed samples.…”
mentioning
confidence: 95%